Empirical investigation of the effects of industry type and firm size on export barriers - Silva, Joaquim Ramos; Franco, Mário; Magrinho, André (Journal of Business Economics and Management, 2016)
This study aims to explore the importance of export barriers and to achieve this by comparing different industry types and firm sizes. We performed a cross-sectional study of 529 Portuguese export firms drawn from the database held by a Portuguese Industrial Association – Business Confederation. From multivariate analysis of variance and the Tukey’s HSD (Honestly Significant Difference) test, we conclude that the more important export barriers mentioned by the firms proved more external than internal. Our results also show that the service and retail trade sectors were the sectors reporting the greatest peculiarities regarding export barriers. Thus, we identify an “industry effect” as regards export barriers even while our findings do not indicate any “size effect”. Knowing the industry-specific export barriers enables companies not only to better coordinate and perform export processes but also to better anticipate the behaviour of their competitors. Other practical and theoretical implications will also be presented.